Weighted norm inequalities for a class of rough singular integrals - H. M. Al-Qassem (International Journal of Mathematics and Mathematical Sciences)
Weighted norm inequalities are proved for a rough homogeneous singular integral operator and its corresponding maximal truncated singular operator. Our results are essential improvements as well as extensions of some known results on the weighted boundedness of singular integrals.